Dmitrii Ivanovich Meyer's contribution to the scientific development of Russian commercial law - V.A. Belov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2019)
In this paper, D.I. Meyer’s two works – “Legal Research on the Commercial Life of Odessa” and “Essay on Russian Law on Bill of Credit” – have been analyzed. The work “Legal Research on the Commercial Life of Odessa” is a thorough scientific elaboration of three areas of customary law (commission agreement, bills of credit, and marine insurance), as well as the first discussion of trade customs in the Russian literature. The work “Essay on Russian Law on Bill of Credit”, in turn, can be characterized as the first experience of posthumous use of notes from students of the lectures delivered by D.I. Meyer. A.I. Vitsyn began to compile and publish the lectures delivered by professors that gradually turned into a course of Russian civil law. D.I. Meyer never worked on this work himself. According to the results of the analysis, the important and been undeservedly forgotten contribution (given the background of more striking successes in the field of civil law teaching) made by D.I. Meyer to the science of Russian commercial law has been revealed. It has been suggested that the title of one of the fathers of Russian civil law should be also supported by D.I. Meyer’s reputation as the “founding father of Russian commercial law”.